2013
DOI: 10.1111/ajt.12224
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Acellular Ex Vivo Liver Perfusion Reduces Liver and Bile Duct Injury of Pig Livers Retrieved After Cardiac Death

Abstract: y Both the authors contributed equally.We compared cold static with acellular normothermic ex vivo liver perfusion (NEVLP) as a novel preservation technique in a pig model of DCD liver injury. DCD livers (60 min warm ischemia) were cold stored for 4 h, or treated with 4 h cold storage plus 8 h NEVLP. First, the livers were reperfused with diluted blood as a model of transplantation. Liver injury was determined by ALT, oxygen extraction, histology, bile content analysis and hepatic artery (HA) angiography. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 30 publications
1
115
0
1
Order By: Relevance
“…Experimental data from large animal studies, specifically investigating biliary epithelial recovery following a period of warm ischemic and NMP, suggest that warm oxygen delivery may provide a critical advantage (29,30). This is a key issue in the quest to increase the utilization of DCD organs in liver transplantation and will only be addressed in the context of a randomized trial with longer-term follow-up of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data from large animal studies, specifically investigating biliary epithelial recovery following a period of warm ischemic and NMP, suggest that warm oxygen delivery may provide a critical advantage (29,30). This is a key issue in the quest to increase the utilization of DCD organs in liver transplantation and will only be addressed in the context of a randomized trial with longer-term follow-up of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Normothermic machine perfusion (NMP) is a preservation technology with potential to prevent both ischemic injury and the deleterious effect of cold temperatures by perfusing organs with a warm oxygenated perfusion solution. Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…60 Normothermic machine perfusion was also shown to reduce liver and bile duct injury in a porcine DCD liver model. 61 Recovery of DCD livers and successful transplant after an extended WIT has also been recorded in rat models. 62 Rat livers subjected to 45 minutes of warm ischemia and 2 hours of cold storage were suc cessfully recovered using normothermic machine perfusion and transplanted.…”
Section: Future Considerationsmentioning
confidence: 92%